Aerobic and resistance exercises in post-operative breast cancer participants at risk of lymphedema: an exploratory study - Mazian, Haniif Ahmad Mazian (2020)
Background and Objectives: Breast cancer related lymphadenopathy (BCL) is a serious problem that affects the activity of daily living, self-esteem and quality of life (Ahmed, 2006). BCL affects a high percentage of post mastectomy and axillary clearance patients.(ACS, 2006) This experimental exploratory study is aimed to see whether a tailored resistance and aerobic exercise applied as early as to weeks post-surgery may prevent the development of upper limb edema and whether it is feasible from the aspect of safety and applicability. Methodology: This is a pilot study, 16 patients fits the inclusion criteria were randomized into two arms. 10 were enrolled in the exercise groups, and 6 designate to the routine physiotherapy group. Subjects in the exercise group were prescribed resistance and aerobic exercise two weeks post-surgery and were required to comply to the regime for six weeks where the parameters were measured again. Results: Significant outcomes were found in the interventional group, the percentage of RLV of Axilla in intervention group (0.56 (2.34)) was significantly lower than percentage of RLV of Axilla in control group (5.03 (2.84)) (p = 0.009) and the percentage of RLV of Middle Upper Arm in intervention group (0.93 (1.84)) was significantly lower than percentage of RLV of Middle Upper Arm in control group (5.66 (10.85)) (p = 0.005). The Arm Fluid Volume in intervention group (3.79 (5.92)) was also significantly lower than the Arm Fluid Volume in control group (22.36 (9.49)) (p = 0.001). Conclusions: We conclude that this study provide positive outcomes as compared to the control group results and it is feasible to be carried out by the patients.